Regulation of expression of growth arrest-specific genes in mouse fibroblasts. - Ciccarelli, C (1990)
The suppression of growth arrest-specific (gas) gene expression by serum appeared to be independent of protein synthesis, but expression in resting cells was sensitive to 2-aminopurine, an inhibitor of intracellular protein kinases. Although accumulation of gas gene mRNA was reduced by serum, nuclear transcription of the gas-2, -3, and -5 genes was observed in serum-stimulated cells, indicating that posttranscriptional events may regulate mRNA levels. Growth induction by serum, on the other hand, led to suppression of transcription of the gas-1 gene. Cell cycle regulation and the serum response of gas-1 were lost in ras-transformed cells.